Reconstruction of the Branch’s Munasabah Ulumul Qur’an - Fadil Fauzan; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
This article discusses the concept of munasabah reconstruction in the ulumul Qur’an branch. The problem is a lack of deep understanding of this concept as well as the need for a more systematic approach to implementing it. The aim is to explore a better understanding of the concept of munasabah reconstruction and provide a clear method for applying it in the study of Qur’anic ulumul. The exegetical method used Is a comprehensive analysis of classical and modern texts that discuss munasabah in the Al-Qur’an, as well as a study of relevant methodological approaches. Through this approach, researchers identify the principles underlying the concept of munasabah reconstruction, such as the relationship between the verses of the Qur’an and the historical context and social environment at the time the revelation was revealed. The results of this research indicate that munasabah reconstruction plays an important role in understanding and interpreting the Qur’an more holistically. By applying these principles, readers can gain a deeper understanding of the messages of the Qur’an and their relevance to the contemporary context. In addition, this article also highlights the importance of developing a more systematic methodology in understanding classical concepts such as munasabah so that they can be applied more effectively in the study of Qur’anic ulumul.